Graph-Based Representation and Reasoning 22nd International Conference on Conceptual Structures, ICCS 2016, Annecy, France, July 5-7, 2016, Proceedings - Haemmerlé, Ollivier; Stapleton, Gem; Faron Zucker, Catherine (Lecture Notes in Artificial Intelligence, 2016)
This book constitutes the proceedings of the 22th International Conference on Conceptual Structures, ICCS 2016, held in Annecy, France, in July 2016. The 14 full papers and 5 short papers presented in this volume were carefully reviewed and selected from 40 submissions. They are organized around the following topical sections: time representation; graphs and networks; formal concept analysis; ontologies and linked data.